Highly specific and selective anti‐pS396‐tau antibody C10.2 targets seeding‐competent tau. Issue 1 (13th October 2018) - Rosenqvist, Nina; Asuni, Ayodeji A.; Andersson, Christian R.; Christensen, Søren; Daechsel, Justus A.; Egebjerg, Jan; Falsig, Jeppe; Helboe, Lone; Jul, Pia; Kartberg, Fredrik; Pedersen, Lars Ø.; Sigurdsson, Einar M.; et al.
Abstract: Introduction: The abnormal hyperphosphorylation of the microtubule‐associated protein tau plays a crucial role in neurodegeneration in Alzheimer's disease (AD) and other tauopathies. Methods: Highly specific and selective anti‐pS396‐tau antibodies have been generated using peptide immunization with screening against pathologic hyperphosphorylated tau from rTg4510 mouse and AD brains and selection in in vitro and in vivo tau seeding assays. Results: The antibody C10.2 bound specifically to pS396‐tau with an IC50 of 104 pM and detected preferentially hyperphosphorylated tau aggregates from AD brain with an IC50 of 1.2 nM. C10.2 significantly reduced tau seeding of P301L human tau in HEK293 cells, murine cortical neurons, and mice. AD brain extracts depleted with C10.2 were not able to seed tau in vitro and in vivo, demonstrating that C10.2 specifically recognized pathologic seeding‐competent tau. Discussion: Targeting pS396‐tau with an antibody like C10.2 may provide therapeutic benefit in AD and other tauopathies.